2020
DOI: 10.31838/jcr.07.04.125
|View full text |Cite
|
Sign up to set email alerts
|

Feedback-Based Gait Identification Using Deep Neural Network Classification

Abstract: Identification of gait plays a major role in the healthcare industry, recognition of a gait having different angles, identification of abnormalities is a challenging task, to detect the abnormal person identification contains improper pattern style, human limbs, walking pattern, etc... A normal person has a correct pattern, an abnormal person has an irregular pattern. This paper provides the identification of the lean angle and ramp angle [19] of irregular patterns on three abnormalities such as Parkinson gait… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Viswanathan and Naib [61] have proposed as Performance parameters used by authors are true positive, true negative and accuracy. Authors make use of various semi-supervised classifiers for intrusion detection.…”
Section:  Issn: 2502-4752mentioning
confidence: 99%
“…Viswanathan and Naib [61] have proposed as Performance parameters used by authors are true positive, true negative and accuracy. Authors make use of various semi-supervised classifiers for intrusion detection.…”
Section:  Issn: 2502-4752mentioning
confidence: 99%
“…They found that average stride length of control group is 37.2 cm which is greater than the stride length of PD group 22.38 cm but gait speed is almost equal in both cases. Early detection of Parkinson diseases (Kondragunta et al, 2019;Mallikarjuna et al,2020) can delay the effect of this disease. For early detection of this disease deep learning algorithms can be used to estimate 2D poses.…”
Section: Introductionmentioning
confidence: 99%